Tiger Nuts: A Revival of an Ancient Egyptian Plant - El-Din, Dina M. Ezz.
The importance of archaeobotany has been widely recognized in recent years, and more research is being conducted to study botanical remains. Only a very few of the cultivated vegetables grown in fields and in gardens were indigenous to Egypt, but one was the tiger nut (Cyperus esculentus L.) which was known and consumed since the Predynastic Period. Remains of dry tiger nuts tubers were found in large quantities in tombs from Neolithic times onwards. Some were found inside the stomachs of bodies as early as the Predynastic Period. Tiger nuts are attested in funerary offering lists, festival offerings, in medicine and in diet. This paper sheds light on the importance of tiger nuts and its different uses. It also urges their use in modern Egypt.